1985
DOI: 10.7567/jjaps.24s2.868
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Phase Transition of VDF/TrFE Copolymer at High Pressures

Abstract: High pressure ultrasonic and D-E hystresis measurements were performed on a vinylidene fluoride-trifluoroethylene (VDF/TrFE) copolymer with 54 mol% VDF content to investigate the pressure effect on physical properties accompanying wiht a ferroelectric phase transition. Differing from the results at atmospheric pressure where the ferro-to-paraelectric phase transition proceeded simply in one-step, this copolymer exhibited at 350 MPa two-step temperature variations in ultrasonic velocity and absorption, and rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Nakanishi, Ohigashi and Minomura ( 1982) reported that the heat treatment at high pressures substantially improved the crystallinity and the piezoelectricity of the copolymer samples. Moreover the present author and his group have conducted DTA, ultrasonic, dilatometric and X-ray measurements on a copolymer sample, and have observed that the nature of the ferroelectric phase transition as well as the ferroelectric crystal structures were altered by the application of pressure Matsushige, Tagashira, Horiuchi, Taki and Takemura, 1985).…”
Section: K Matsushigementioning
confidence: 97%
“…Nakanishi, Ohigashi and Minomura ( 1982) reported that the heat treatment at high pressures substantially improved the crystallinity and the piezoelectricity of the copolymer samples. Moreover the present author and his group have conducted DTA, ultrasonic, dilatometric and X-ray measurements on a copolymer sample, and have observed that the nature of the ferroelectric phase transition as well as the ferroelectric crystal structures were altered by the application of pressure Matsushige, Tagashira, Horiuchi, Taki and Takemura, 1985).…”
Section: K Matsushigementioning
confidence: 97%
“…The effect of pressure on the 54/46 VDF/TrFE copolymer has been studied. 124,125 This was done using a set of methods including DSC, X-ray diffraction, D ± E hysteresis, and ultrasonic studies. The temperature dependences of a number of parameters determined by these methods are shown in Fig.…”
Section: The Influence Of Pressure On the Characteristics Of The Ferr...mentioning
confidence: 99%
“…This unusual phenomenon can be interpreted based on the above hypothesis concerning the formation of two types of ferroelectric phase, LT and QL, in the copolymers considered. 124,126 It is assumed that under normal pressure, crystallisation proceeds in the QL phase, whereas at the Curie point, the QL phase transforms in one step into the paraelectric phase. As the pressure increases to 350 MPa at room temperature, the QL ferroelectric phase transforms into a more perfect phase, LT.…”
Section: The Influence Of Pressure On the Characteristics Of The Ferr...mentioning
confidence: 99%
See 1 more Smart Citation